A study on the relationship of broken family and unhappy, unbroken family on the popularity of adolescents of V&G Subdivision, Tacloban City - Natan, Priscilla Joy G. (1999)
The study aimed to determine if there is a significant difference on the popularity of adolescent from broken homes and unhappy, unbroken homes in V&G Subdivision, Tacloban City. A total of 42 respondents, 21 from the broken homes and 21 from unhappy, unbroken homes were selected. The questionnaire was used to gather the needed data. After the retrieval of the questionnaires, the researcher tabulated the data. The results showed that since obtained t= 1.92 which is lesser than the tabulated value of t= 2.021 at .05 level, the null hypothesis is accepted that there is no significant difference between the popularity level of adolescents from broken homes and unhappy, unbroken homes.